Mathematics

Question

What is the value of h(−3) when h(x)= 6x2 − 2x + 12?
a. −306
b. −36
c. 48
d.72
e. 342

2 Answer

  • What you would do is plug in -3 where x is.
    h(x)=6(-3)*2-2(-3)+12
    You then would solve the equation.
    *Remember P.E.M.D.A.S.*
    6(-3)*2-2(-3)+12  - Multiply 6(-3) & 2(-3) together.
    -18*2-6+12 - Multiply -18*2 together.
    -36-6+12 -Add 12 to -36
    -24-6 -Subtract
    -30

    Hope This helps! :)
  • Answer:

    72

    Step-by-step explanation:

    Parentheses Exponents Multiplication Division Addition Subtraction

    h(-3) = 6(-3)^2 - 2(-3) + 12

    E h(-3) = 6(9) - 2(-3) + 12

    M h(-3) = 54 - (-6) +12

    A h(-3) = 66 - (-6)

    S h(-3) = 72

NEWS TODAY